Ответ:
Упростить выражение .
Применяем формулы разности квадратов и квадрата разности .
[tex]\bf \dfrac{0,04m^2-1}{0,04m^2-0,4m+1}=\dfrac{(0,2m)^2-1^2}{(0,2m)^2-2\cdot 0,2m\cdot 1+1^2}=\\\\\\=\dfrac{(0,2m-1)(0,2m+1)}{(0,2m-1)^2}=\dfrac{0,2m+1}{0,2m-1}[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Упростить выражение .
Применяем формулы разности квадратов и квадрата разности .
[tex]\bf \dfrac{0,04m^2-1}{0,04m^2-0,4m+1}=\dfrac{(0,2m)^2-1^2}{(0,2m)^2-2\cdot 0,2m\cdot 1+1^2}=\\\\\\=\dfrac{(0,2m-1)(0,2m+1)}{(0,2m-1)^2}=\dfrac{0,2m+1}{0,2m-1}[/tex]